Interplay between NO Signalling, ROS, and the Antioxidant System in Plants - Violeta Velikova (Frontiers Research Topics, 2017)
Over the last decades, nitric oxide (NO) has emerged as an essential player in redox signalling. Reactive oxygen species (ROS) also act as signals throughout all stages of plant life. Because they are potentially harmful for cellular integrity, ROS and NO levels must be tightly controlled, especially by the classical antioxidant system and additional redox-active metabolites and proteins. Recent work provided evidence that NO and ROS influence each other's biosynthesis and removal. Moreover, novel signalling molecules resulting from the chemical reaction between NO, ROS and plant metabolites have been highlighted, including N2O3, ONOO-, NO2, S-nitrosoglutathione and 8-NO2 cGMP. They are involved in diverse plant physiological processes, the best characterized being stomata regulation and stress defense. Taken together, these new data demonstrate the complex interactions between NO, ROS signalling and the antioxidant system. This Frontiers in Plant Science Research Topic aims to provide an updated and complete overview of this important and rapidly expanding area through original article and detailed reviews.